2020
DOI: 10.1097/pgp.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Diagnostic Algorithm for the Diagnosis of Intraepithelial Fallopian Tube Lesions

Abstract: Intraepithelial fallopian tube neoplasia is thought to be a precursor lesion to high-grade serous carcinoma of the Müllerian adnexae, particularly in women with BRCA1 or BRCA2 mutations. This association has led to recommendations to assess fallopian tubes for intraepithelial atypia. However, the diagnostic reproducibility of a diagnosis of intraepithelial neoplasia is unclear. In this study, 2 gynecologic pathologists independently evaluated sections of fallopian tubes from a sample of women (N=198, 623 slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…These lesions are alternatively described as fallopian tube intraepithelial neoplasia or high-grade tubal intraepithelial lesions, to specifically denote noninvasive lesions. 23…”
Section: Introductionmentioning
confidence: 99%
“…These lesions are alternatively described as fallopian tube intraepithelial neoplasia or high-grade tubal intraepithelial lesions, to specifically denote noninvasive lesions. 23…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a STIC and a positive cytology were also included to maintain consistency with previous publications on this subject ( 7 ). Serous intraepithelial neoplasia is also known as STIC and was included ( 18 ). Study exclusion criteria for review were missing clinical data (follow-up) and publications restricted to pathological information only.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological features for diagnosing STIC have been variably applied by pathologists, 6 and studies have shown that establishing a diagnosis using only morphology does not have high interobserver reproducibity. [17][18][19][20] Thus, a diagnostic algorithm that incorporates histological features coupled with immunohistochemical results for p53 and Ki-67 (Figure 3) was previously developed to aid the classification of epithelial atypias of the fallopian tube, which improves the reproducibility of diagnosing STIC 18,19,21 and allows lesions to be categorised as STIC, atypical lesions intermediate between STIC and p53 signature (serous tubal intra-epithelial lesion [STIL]; lesions analogous to STIL have been described by various terms in other publications, such as dysplasia, tubal intra-epithelial lesion in transition and dormant STIC [the designation dormant STIC has been used in other studies to designate lesions with significant atypia and aberrant p53 expression but without a high Ki-67 proliferation index (see below for thresholds separating low from high indices)] and p53 signature (see Pathogenesis section below). As diagnostic criteria for this continuum of atypical lesions have not been standardised, use of such an algorithm will help with communication among pathologists, clinicians and researchers.…”
Section: Combined Use Of Histological and Immunohistochemical Feature...mentioning
confidence: 99%